Carbon Purchase Agreements, Dactories, and Supply-Chain Innovation: What Will It Take to Scale-Up Modular Direct Air Capture Technology to a Gigatonne Scale - Izikowitz, David (Frontiers in Climate, 2021)
Natural and engineered carbon dioxide removal have become regular features of climate models which limit warming to 1.5°C or even 2°C above pre-industrial levels. This gives rise to an assumption that solutions, for example Direct Air Capture (DAC) - involving the direct removal of carbon dioxide from ambient air - can be commercialised and deployed at the necessary speed and scale to have a material impact, on the order of gigatonnes, by mid-century. Modular, solid-sorbent DAC, with a modular, solid sorbent approach on a gigatonne scale, will require the mass mobilisation of supply-chains to manufacture millions of modular DAC units - 20 million of the present state of the art 50 tonne/year modules to deliver one gigatonne per year, as well as the large-scale production of novel chemical sorbents. To achieve a climate relevant DAC industry will demand innovative procurement models, for example carbon purchase agreements, and dedicated DAC manufacturing facilities, (or Dactories). In addition, insight is offered through the work of China-based DAC start-up Carbon Infinity into the industry supply-chain position, adopting lessons from computing and energy technologies. In particular, we look at approaches and financing models to drive demand and scale-up DAC module production, and opportunities presented in the development of an integrated DAC manufacturing industry.